Unmasking the pituitary shadow 11 years postpartum: A case report of late-stage Sheehan's syndrome - Oumaima Mesbah; Ola Messaoud; Badr Kabila; Omar EL aoufir; Laila Jroundi; Zaynab Iraqi Houssaini (Radiology Case Reports)
Sheehan's syndrome (SS) is a rare but significant condition that occurs as a result of postpartum pituitary gland infarction, typically following severe blood loss or hypotension during or after childbirth. The syndrome is characterized by signs of anterior pituitary insufficiency, including deficiencies in hormones such as cortisol, thyroid hormones, and gonadotropins. The diagnosis of this rare but potentially fatal disease is often delayed due to the vague symptoms and the insidious nature of pituitary dysfunction. It is typically confirmed through hormonal assays and imaging, which reveal anatomical changes in the pituitary gland, such as atrophy or empty sella syndrome, supporting the diagnosis. Treatment of Sheehan's syndrome primarily involves hormone replacement therapy to correct the endocrine imbalances, to prevent adrenal crises and other complications. We present the case of a 40-year-old woman, 11 years postpartum, who was hospitalized for a severe infection, revealing a pituitary dysfunction due to a delayed revelation of Sheehan's syndrome.